An Analysis of Teachers' Strategies in Teaching English in Blended Learning Situations to Eleventh-Grade Students of SMAN 4 Palu - R. Kaning, Sri Alfidayati; Fitriningsih, Fitriningsih; Afifah, Afifah (Datokarama English Education Journal, 2023)
This research discussed an Analysis of Teachers’ Strategies in Teaching English in Blended Learning Situation at Eleventh Grade Students of SMAN 4 Palu. The research question of this research are: (1) what strategy do teachers use in teaching English in a blended learning situation to eleventh-grade students of SMAN 4 Palu? (2) how is the implementation of the strategies in teaching English in blended learning situations to eleventh-grade students of SMAN 4 Palu?. In this research, the researcher used qualitative descriptive research, with case study research type. Technique of data collection through (1) observation, (2) interview, (3) questionnaire, and (4) documentation. Technique of data analysis are data collection, data reduction, data display, and conclusion. Checking data validity was conducted with (1) credibility, (2) transferability, (3) dependability, and (4) confirmability (Objectivity). The results of this research showed that the strategy that teachers use in teaching English in blended learning situations in class XI is vocabulary building, cooperative learning, and students chosen text. Based on the results of the questionnaire given to students, by using the Likert scale technique, about 77% category agree or good. It means the students’ response to the teacher in teaching English in blended learning situation at eleventh grade students of SMAN 4 Palu is good and able to help students in learning English. Students like the way of teaching of the English teachers.